2023
DOI: 10.1021/acsomega.3c05860
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Evaluation of a New Series of 2-Pyrazolines as Potential Antileukemic Agents

Mehlika Dilek Altıntop,
Zerrin Cantürk,
Ahmet Özdemir

Abstract: In an attempt to identify small molecules for the treatment of leukemia, 12 new pyrazolines (2a−l) were synthesized efficiently. WST-1 assay was performed to examine their cytotoxic features on HL-60 human acute promyelocytic leukemia (APL), K562 human chronic myeloid leukemia (CML), and THP-1 human acute monocytic leukemia cells. Four compounds (2e, 2f, 2g, and 2h) were determined as promising antileukemic agents on HL-60 and K562 cells. IC 50 values of compounds 2f, 2h, 2e, 2g, and bortezomib for the HL-60 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…The absence of this band in the IR spectra of compounds 2a – l revealed that the cyclization reaction occurred efficiently for the formation of the pyrazoline ring. The 1 H NMR spectra of compounds 2a – l confirmed the presence of the ABX pattern (Figure ), which is a characteristic feature of the 1 H NMR spectra for the 2-pyrazoline core . In their 1 H NMR spectra, the H A , H B, and H X protons of the pyrazoline ring gave rise to the doublet of doublets at 3.00–3.14, 3.78–3.90 and 5.21–5.51 ppm, respectively, with J AB = 16.15–17.65 Hz, J BA = 17.25–17.65 Hz, J AX = 4.70–7.20 Hz, and J BX = 11.80–12.05 Hz.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…The absence of this band in the IR spectra of compounds 2a – l revealed that the cyclization reaction occurred efficiently for the formation of the pyrazoline ring. The 1 H NMR spectra of compounds 2a – l confirmed the presence of the ABX pattern (Figure ), which is a characteristic feature of the 1 H NMR spectra for the 2-pyrazoline core . In their 1 H NMR spectra, the H A , H B, and H X protons of the pyrazoline ring gave rise to the doublet of doublets at 3.00–3.14, 3.78–3.90 and 5.21–5.51 ppm, respectively, with J AB = 16.15–17.65 Hz, J BA = 17.25–17.65 Hz, J AX = 4.70–7.20 Hz, and J BX = 11.80–12.05 Hz.…”
Section: Resultsmentioning
confidence: 52%
“…The 1 H NMR spectra of compounds 2a – l confirmed the presence of the ABX pattern ( Figure 3 ), which is a characteristic feature of the 1 H NMR spectra for the 2-pyrazoline core. 34 In their 1 H NMR spectra, the H A , H B, and H X protons of the pyrazoline ring gave rise to the doublet of doublets at 3.00–3.14, 3.78–3.90 and 5.21–5.51 ppm, respectively, with J AB = 16.15–17.65 Hz, J BA = 17.25–17.65 Hz, J AX = 4.70–7.20 Hz, and J BX = 11.80–12.05 Hz. In the 13 C NMR spectra of compounds 2a – l , the signals were observed in the region 150.66–150.91, 44.28–44.65, and 61.89–64.00 ppm corresponding to the C3, C4, and C5 carbons of the pyrazoline skeleton, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation